2001
DOI: 10.1038/sj.onc.1204668
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms for aberrant expression of the human breast cancer specific gene 1 in breast cancer cells: control of transcription by DNA methylation and intronic sequences

Abstract: Breast cancer speci®c gene 1 (BCSG1), also referred as synuclein g, is the third member of a neuronal protein family synuclein. BCSG1 is not expressed in normal breast tissues but highly expressed in advanced in®ltrat-ing breast carcinomas. When over expressed, BCSG1 signi®cantly stimulates breast cancer metastasis. To elucidate the molecular mechanisms underlying the abnormal transcription of BCSG1 in breast cancer cells, in this study, we isolated a 2195 base pair fragment of human BCSG1 gene. This fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 16 publications
2
63
0
Order By: Relevance
“…Since BubR1 is a critical component of the mitotic checkpoint control, it could be a potential cellular target of oncogenic proteins such as BCSG1 that induces tumor progression potentially through mechanisms of disturbing genome stability. To confirm BCSG1 and BubR1 interaction in mammalian cells, initially we performed immunoprecipitation (IP) assay using total cell lysates isolated from a BCSG1-positive cell line T47D and a BCSG1-negative cell line HepG2 (Lu et al, 2001). Using BCSG1-specific antibody to IP, BubR1 was only detected in the IP complex of T47D cells ( Figure 1a, lane 2) but not in the IP complex formed with the HepG2 cell lysate (Figure 1a, lane 4), despite the detection of BubR1 protein in the total cell lysate of HepG2 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Since BubR1 is a critical component of the mitotic checkpoint control, it could be a potential cellular target of oncogenic proteins such as BCSG1 that induces tumor progression potentially through mechanisms of disturbing genome stability. To confirm BCSG1 and BubR1 interaction in mammalian cells, initially we performed immunoprecipitation (IP) assay using total cell lysates isolated from a BCSG1-positive cell line T47D and a BCSG1-negative cell line HepG2 (Lu et al, 2001). Using BCSG1-specific antibody to IP, BubR1 was only detected in the IP complex of T47D cells ( Figure 1a, lane 2) but not in the IP complex formed with the HepG2 cell lysate (Figure 1a, lane 4), despite the detection of BubR1 protein in the total cell lysate of HepG2 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis indicates that the exon 1 region contains a CpG island. In vivo genomic bisulfite sequencing demonstrates that the BCSG1 CpG island is totally unmethylated in BCSG1-positive SKBR-3 and T47D cells but partially methylated in BCSG1-negative MCF-7 and HepG2 cells (7). This suggests that DNA demethylation may be an important factor contributing to the aberrant expression of BCSG1 in breast cancer cells.…”
mentioning
confidence: 90%
“…However, the promoter reporter activity was markedly increased by inclusion of the intron 1 region of the BCSG1 gene. Further deletion analysis localized a consensus AP1 binding site (TGACTCA) in the intron that was largely responsible for the increased promoter activity (7). These previous studies suggest that the activator protein AP1 may regulate BCSG1 transcription, possibly through the intronic AP1 binding site.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The SNCG expression in lung tumors shows a correlation with stage progression and metastasis. The exon 1 of SNCG gene contains a CpG island with 15 CpG dinucleotides (Lu et al, 2001). By performing genomic sequencing and methylation-specific polymerase chain reaction (MSP) assays, we have shown that the SNCG CpG island is completely unmethylated in lung tumor samples as well as in other types of tumors, which is in sharp contrast to the predominantly methylated CpG island of SNCG in the majority of normal tissues adjacent to tumors (Liu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%